Learners’ Perceived Self-Efficacy, Engagement, and Satisfaction in Online Learning of Accounting and Auditing University Students (Journal of Contemporary Educational Policies and Practices, 2022)
The development of online learning is inevitable in the digital age and the Covid-19 pandemic context. The benefits and limitations of online learning are studied along with solutions to improve its efficiency. This study investigated how students’ perceived self-efficacy affects their learning online learning environment based on learner characteristics. With the data collected from 401 accounting and auditing students, the study evaluated the measurement model and tested the research hypotheses with the structural equation model (SEM), SPSS 20 and Amos 24. The finding validates that the level of online student engagement can be classified as: engagement for learning and engagement for social interaction. The results of the SEM analysis show a significant positive influence of online students’ perceived self-efficacy on their engagement in learning and on the satisfaction of students majoring in accounting and auditing. These findings contribute to the existing literature and practice that provide a framework for higher education to propose appropriate solutions to promote online learning or blended learning.
Keywords: Accounting and auditing student; online learning; online student engagement; perceived self-efficacy; satisfaction